MiR-222-3p is involved in neural tube closure by directly targeting Ddit4 in RA induced NTDs mouse model. Issue 22 (17th November 2021) - Sun, Yuqing; Zhang, Juan; Wang, Yufei; Wang, Lei; Song, Meiyan; Khan, Ajab; Zhang, Li; Niu, Bo; Zhao, Hong; Li, Meining; Luo, Tiane; He, Qiwei; et al.
ABSTRACT: Previously our results showed miR-222-3p was significantly downregulated in retinoic acid-induced neural tube defect (NTD) mouse model through transcriptome. Down-regulation of miR-222-3p may be a causative biomarker in NTDs. In this study, RNA was extracted from mouse embryos at E8.5, E9.5 and E10.5, and the expression level of miR-222-3p was measured by quantitative real-time PCR analysis. The preliminary mechanism of miR-222-3p in NTDs involved in cell proliferation, apoptosis and migration was investigated in mouse HT-22 cell line. The expression of miR-222-3p was significantly decreased at E8.5, E9.5 and E10.5 developed in mouse embryos which were consistent with our transcriptome sequencing. Suppression of miR-222-3p in HT-22 cells resulted in the inhibition of cell proliferation and migration, cell cycle and apoptosis. Moreover, DNA damage transcript 4 (Ddit4) was identified as a direct and functional target of miR-222-3p. miR-222-3p is negatively regulated by Ddit4. The mutation of binding site of Ddit4 3ʹUTR abrogated the responsiveness of luciferase reporters to miR-222-3p and showed that Ddit4 expression partially attenuated the function of miR-222-3p. We preliminatively confirmed that low expression of miR-222-3p has reduced the expression of β-catenin, TCF4 and other related genes in the Wnt/β-catenin signaling pathway. Collectively, these results demonstrated that miR-222-3p regulates the Wnt/β-catenin signaling pathway through Ddit4 inhibition in HT-22 cells, resulted in cell proliferation and apoptosis imbalance, and thus led to neural tube defects.